A systematic review and meta-analysis: Biomechanical evaluation of the effectiveness of strength and conditioning training programs on front crawl swimming performance - Kwok, W. Y.; So, B. C. L.; Tse, D. H. T.; Ng, S. S. M. (Journal of Sports Science & Medicine, 2021)
The objectives of this systematic review were to summarize and evaluate the effectiveness of strength and conditioning trainings on front crawl swimming, starts and turns performance with relevant biomechanical parameters. Four online databases including PudMed, ESCSOhost, Web of Science and SPORTDiscus were searched according to different combination of keywords. 954 articles were extracted from databases, and ultimately 15 articles were included in this study after removal of duplicate and articles screening according to inclusion and exclusion criteria. Meta-analyses were adopted when appropriate and Egger`s regression symmetry was adopted to assess the publication bias and the results were presented with forest plots and funnel plots respectively. Fifteen articles studied the effects of strength and resistance, core, and plyometric trainings. The quality of the investigation was assessed by the checklist developed by Downs and Black. Most of the investigations found out that training programs were beneficial to front crawl sprinting swimming performance, stroke biomechanics, force, and muscle strength. First, strength and resistance trainings and core trainings were effective on sprinting performance enhancement. Second, resistance trainings were found to have positive effects on stroke rate. Plyometric trainings were beneficial to start performance, while there was no sufficient evidence for confirming the positive improvement on turn biomechanical, also overall swimming performance, after weeks of plyometric trainings. Strength and Conditioning trainings are suggested to implement in regular training regime regarding to the positive effects on swimming performance, including starts, turns and front crawl swim, and relevant biomechanical parameters, instead of swimming training only. Further research with higher quality is recommended to conduct and more investigations on the training effects to other stroke styles are also suggested.